How Local Culture and Memorable Tourism Experiences Drive Sustainable Tourism: The Mediating Role of Destination Satisfaction in the Ijen Mountains, Banyuwangi Indonesia - Endang Suprihatin; Rais Dera Pua Rawi; Endah Susanti (Vifada Management and Social Sciences, 2026)
Purpose: This study aims to analyze the influence of local culture and memorable tourism experiences on sustainable tourism by placing destination satisfaction as a mediating variable in the Ijen Mountains destination of Banyuwangi. Research Design and Methodology: This study uses a quantitative approach with a fundamental research type. The research object was conducted in the Ijen Mountains of Banyuwangi with respondents consisting of tourists and local residents. Data were analyzed using the PLS-SEM method to test the predictive relationship between constructs, as well as to ensure the validity and reliability of the research instrument. Findings and Discussion: This study concludes that local culture and memorable tourism experiences have a significant influence on sustainable tourism both directly and through destination satisfaction as a mediating variable. Local culture is a key foundation for sustainable tourism development through the preservation of cultural values ​​and community involvement. While memorable tourism experiences increase tourist satisfaction and engagement with destinations, encouraging sustainable travel behavior. Implications: Tourism destination managers need to prioritize strengthening local cultural management as a key strategy in developing sustainable tourism. Future research is recommended to expand the research object to various tourist destinations and develop models by adding other relevant variables.